2000
DOI: 10.1093/pcp/41.4.448
|View full text |Cite
|
Sign up to set email alerts
|

A Tobacco NtMET1 cDNA Encoding a DNA Methyltransferase: Molecular Characterization and Abnormal Phenotypes of Transgenic Tobacco Plants

Abstract: A cDNA encoding a DNA methyltransferase, with a predicted polypeptide of 1556 amino acid residues containing all motifs conserved in this enzyme family, was isolated from tobacco plants, and the corresponding gene was designated as NtMET1. RNA blot analysis indicated NtMET1 transcripts to accumulate in dividing tissues of tobacco plants, and they could be detected during the S phase in synchronized dividing BY2 cells. In situ hybridization revealed the transcripts to be localized exclusively in actively prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 24 publications
5
41
0
1
Order By: Relevance
“…MET1 homologues have been characterized in various plants, such as carrot, pea, tobacco, maize, and rice (Bernacchia et al 1998, Nakano et al 2000, Pradhan et al 1998, Teerawanichpan et al 2004, while CMT family members have been identified only in A. thaliana and maize (Lindroth et al 2001, Bartee et al 2001, Papa et al 2001. In the present study, three DNA methyltransferase genes were obtained from B. rapa and structural conservation was observed between BrMET1a/ BrMET1b and AtMET1 and between BrCMT and AtCMT3, suggesting that these three isolated genes may function as DNA methyltransferase genes.…”
Section: Discussionsupporting
confidence: 52%
“…MET1 homologues have been characterized in various plants, such as carrot, pea, tobacco, maize, and rice (Bernacchia et al 1998, Nakano et al 2000, Pradhan et al 1998, Teerawanichpan et al 2004, while CMT family members have been identified only in A. thaliana and maize (Lindroth et al 2001, Bartee et al 2001, Papa et al 2001. In the present study, three DNA methyltransferase genes were obtained from B. rapa and structural conservation was observed between BrMET1a/ BrMET1b and AtMET1 and between BrCMT and AtCMT3, suggesting that these three isolated genes may function as DNA methyltransferase genes.…”
Section: Discussionsupporting
confidence: 52%
“…MET1 mutants exhibit drastically decreased DNA methylation levels and morphological abnormalities (Finnegan et al 1996;Ronemus et al 1996;Kankel et al 2003). A similar reduction of global methylation and altered phenotypes were also observed in transgenic tobacco plants in which DNA methylation levels were suppressed by expression of anti-sense NtMET1, which encodes a maintenance DNA methyltransferase in tobacco plants (Nakano et al 2000). Subsequent screening of genes whose expression was specifically affected in these transgenic plants, revealed more than half to be related to stress responses.…”
Section: Methyltransferasementioning
confidence: 52%
“…The second family contains chromomethylase (CMT) and the third features the domains rearranged methyltransferase (DRM). These enzymes have already been identified from a variety of plants, including maize, tobacco and rice (Finnegan and Denis 1993;Genger et al 1999;Olhoft 1998;Steward et al 2000;Nakano et al 2000;Bernacchia et al 1998;Pradhan et al 1998;Henikoff and Comai 1998;Rose et al 1998;Lindroth et al 2001;Bartee et al 2001;Tompa et al 2002;Papa et al 2001;Cao et al 2000;Wada et al 2003) (Table 2). In the following sections, I briefly summarize their properties and also findings with mutants for chromatin remodeling factors, which govern the global methylation status created by these enzymes.…”
Section: Dna Methylation In Mammalsmentioning
confidence: 98%
“…MET1 is homologous to mammalian Dnmt1 (9), and its suppression results in a drastic reduction of global methylation in transgenic Arabidopsis (10,11). A similar reduction of global methylation and altered phenotypes was also observed in transgenic tobacco plants expressing an antisense tobacco MET1 (NtMET1) gene (12). Thus, MET1 has been suggested to function in maintenance of global genomic methylation in plants (10 -12).…”
mentioning
confidence: 87%